Evaluation of the elite sports result from the viewpoint of different types of public - Kolar, E.; Bednarik, J.; Bubanj, R.; Kovac, M. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2008)
A sports result fulfils its true goal only after monitoring the public and its response, and thus the result acquires additional important dimensions. The significance of a sports result is most often evaluated intuitively and on the basis of emotional reactions and beliefs about its importance on a national and not the worldwide level. An analysis of the evaluation of an elite sports result, achieved at the most important competitions, reveals that various types of public value sports results differently. A sports result is significantly more appreciated by the general and expert public, whilst journalists appreciate it the least. The latter strive to remain objective even when reporting about a one off event, such as major sports event; nevertheless, at the same time they do not sufficiently recognise that an important achievement is the product of a long term training process. The expert public appreciates a competitive sports result more than journalists; presumably, this is a result of the understanding of the importance of the prior training process for the competition achievement. The general public appreciates a sports result the most, which indicates two things - firstly, although media can create public opinion, it has a small influence on the general public; secondly, the results are appreciated mostly on an emotional basis, caused by the road to success and not only by the moment of the achievement of success. Obviously people long for "stories" as well as for "heroes". Thus far the media has not been able to provide these stories for the public.